Resources selection for agile-ivirtual enterprises: part i - model for value analysis integration - Pires, António (2011)
The markets globalization requires companies to continually invest in innovation, competitiveness and excellence. It is important to create a value culture in companies, through methods such as Value Analysis (VA). Nowadays a product is often produced with contributions from several companies and the concept of Agile/Virtual Enterprises (A/V E) emerged and developed. In this work, we propose an activity model of VA integration in the resources pre-selection process for AN E. It was made a literary revision of the existent models of resources selection in AN E in order to identify the main limitations and gaps of the process and assess the relevance of our work. We built the VA integration activity model and defined the VA stages to incorporate in the pre-selection process. An integration of a methodology of the type of VA will be able to incorporate surplus value in this process and leads to a better dynamic organizational integration. The VA integration brings a systematic and organized process in order to guarantee a higher value and more confidence in the resources system, contributing to a more sustainable configuration process of the AN E.